Optimization of lightweight front lower control arm using aluminium cast for C-Segment passenger vehicle - Abdul Rahman, Mohd Hafizi (2021)
In recent years, automakers are concerned with the amount of carbon dioxide released by the vehicle. To overcome this, some components of the vehicle can be reduced in terms of their weight which will result in less production of carbon dioxide. This research is requested by Proton as one of the vehicle weight reduction project. With such aim, this study was conducted to reduce the weight of front lower control arm (FLCA) for C-segment passenger car by cutting down about 20% percent of their weight using the method of optimization process and by using lightweight material as target set by Proton. The concept design of FLCA underwent the optimization process using topology optimization process to eliminate the excessive weight of the part. Then, the optimized design of FLCA was tested for structural strength and fatigue analysis to evaluate the performance of the part. The optimized design results achieved 39% of weight reduction compared to conventional design. It is fulfilling all the structural strength and fatigue analysis performance criteria. The performance for both criteria is on par with the current conventional FLCA. The sand casting process with secondary heat treatment, T6 process was used to fabricate the final design of the FLCA. The final product of aluminium cast FLCA achieved weight 3.20 kg which about 22.14% weight reduction compared conventional FLCA weight 4.11 kg. The fabricated product was tested for fatigue test using the Proton standard, PES-7029 and also mechanical testing to evaluate the structural and microstructural performance of aluminium cast FLCA. From the analysis of hardness, scanning electron microscope, and tensile test, it was shown that aluminium LM 25 has increased the hardness after the T6 heat treatment. Tensile test also showed an increase in ultimate tensile strength and elongation to fracture of heat-treated aluminium LM 25. From the research outcome, the new optimize design of aluminium cast FLCA fulfils all the criteria which are lightweight, very good strength as well as durability performance.